The role of the nurse educator in acute care hospitals Australia - Sayers, Jan Maree (Curtin University, 2013)
The health workforce is one of the critical issues facing contemporary Australian health care systems. Therefore carefully defining roles in the health care system is of great importance. The Role of the Nurse Educator in Australian Acute Care Hospitals study used a mixed-method research design to develop a performance self-assessment scale for nurse educators and describe instances of role ambiguity and conflict. These findings will facilitate comprehensive understanding and integration of nurse educator roles throughout healthcare and education.